Komunikasi Interpersonal dalam Membangun Bonding antara Pengasuh dan Anak Penyandang Disabilitas: Studi Kasus di Panti Asuhan Bhakti Luhur Desa Baumata - Ceciliana Theresa Gat; Veki Edizon Tuhana; Sharon Claudia Rambu Podu Diah (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
Interpersonal communication is the main foundation in the process of communication and interaction in life, including in the context of caregivers and children with disabilities at orphanages, enabling the creation of emotional closeness, also known as bonding. This study uses a qualitative approach with data collection methods through interviews, participatory observation, and documentation studies. The results of this study illustrate that the interaction process between caregivers and children with disabilities occurs through interpersonal communication involving the use of verbal and nonverbal communication. In addition, emotional closeness through the communication process does not form immediately, but rather through stages leading to emotional closeness established in the interaction between caregivers and children with disabilities at the Bhakti Luhur Orphanage in Baumata Village. Nevertheless, in the interaction process, there are certainly obstacles that disrupt the effectiveness of communication and interaction, namely limitations in resources, learning challenges in interacting with children with special needs, and communication problems such as miscommunication. However, all of these can be overcome by caregivers who strive to become parental figures for children with disabilities through evaluation processes and intensive approaches with each child.